2016
DOI: 10.1186/s12882-016-0229-3
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disordered breathing and cardiovascular risk in older patients initiating dialysis in the United States: a retrospective observational study using medicare data

Abstract: BackgroundSleep disordered breathing (SDB) such as sleep apnea is associated with cardiovascular disease in the general population. However, little is known about the cardiovascular risks of SDB in patients with end-stage renal disease (ESRD).MethodsWe identified Medicare fee-for-service beneficiaries aged ≥67 years initiating dialysis between 2004 and 2009. Outcomes of interest included all-cause mortality, incident myocardial infarction, ischemic stroke, and atrial fibrillation. We compared patients with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Three studies compared cardiovascular outcomes in patients with atrial fibrillation according to presence/absence of OSA [62][63][64]. A retrospective study assessed incident stroke in patients with previously diagnosed OSA and end-stage renal disease [65]. A retrospective study analysed the incidence of stroke in community-dwelling men who underwent comprehensive sleep studies [66].…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“…Three studies compared cardiovascular outcomes in patients with atrial fibrillation according to presence/absence of OSA [62][63][64]. A retrospective study assessed incident stroke in patients with previously diagnosed OSA and end-stage renal disease [65]. A retrospective study analysed the incidence of stroke in community-dwelling men who underwent comprehensive sleep studies [66].…”
Section: Results Of Literature Searchmentioning
confidence: 99%
“… 123 , 124 However, in a claims-based study of older patients in the USA, sleep-disordered breathing in haemodialysis patients was not associated with AF. 125 …”
Section: Rate Vs Rhythm Control Of Atrial Fibrillationmentioning
confidence: 99%
“…In addition, overweight/obesity may play a role in the discrepancies as obesity may be a confounding factor in the associations of OSA with CVD in general, and some of the previous studies did not accurately ascertain BMI or the diagnosis of overweight and obesity. Interestingly, patients with sleep-disordered breathing by ICD-9 had a significantly higher BMI, and in the outcomes models that were adjusted for BMI, sleep-disordered breathing diagnosis was associated with an increased risk of death and atrial fibrillation [30]. In the analysis that examines BMI as an exposure in our study, BMI plays a protective role against cardiovascular mortality and hence appears to be a negative confounder of the associations.…”
Section: Discussionmentioning
confidence: 80%
“…In incident peritoneal dialysis patients, a diagnosis of sleep apnea by polysomnography (measuring both obstructive and central apneic events) was associated with an increased risk of all-cause mortality and cardiovascular events [25]. On the other hand, a recently published report provides contradictory information [30]. The investigators studied 184,217 Medicare recipients older than 67 years of age who were initiating dialysis and found that a diagnosis of sleep-disordered breathing as determined by the international classification of disease, ninth version (ICD-9) was associated with a slightly lower risk of death, myocardial infarction, and ischemic stroke.…”
Section: Discussionmentioning
confidence: 99%